2015
DOI: 10.1097/jpo.0000000000000074
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Reliability of the Universal Goniometer in Measurement of Lower-Limb Range of Motion

Abstract: Introduction: The universal goniometer (UG) is commonly used in clinical practice to measure lower limb joint range of motion (ROM). Reliability of the UG is essential to ensure consistency of measurement between and within practitioners. Clinically, it is important to understand how reliability may be affected by various factors. Methods: An electronic and manual literature search was conducted to determine the reliability of the UG. A variety of search terms were used to search between 1980 and July 2015. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(167 reference statements)
0
1
0
Order By: Relevance
“…Universal standard goniometers have shown good validity and reliability but are prone to errors involving method standardisation and tester expertise [20]. There is currently no standard method of using a universal goniometer to measure the angles of the L5-S1 joints.…”
Section: Discussionmentioning
confidence: 99%
“…Universal standard goniometers have shown good validity and reliability but are prone to errors involving method standardisation and tester expertise [20]. There is currently no standard method of using a universal goniometer to measure the angles of the L5-S1 joints.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that the laser goniometer capable of providing high precision, accuracy, and consistency in measuring the involved movements repeatedly. The factor of long practical experience and training of the examiner and the good standardization each procedure of each measurement help to leading for these high-reliability correlation coefficient values [14].…”
Section: Discussionmentioning
confidence: 99%